2008
DOI: 10.1121/1.2934607
|View full text |Cite
|
Sign up to set email alerts
|

Circumaural transducer arrays for binaural synthesis

Abstract: Binaural cues such as the interaural time and level differences are the primary cues for estimation of the lateral position of a sound source, but are not sufficient to determine elevation or the exact position on the "cone of confusion". Spectral content of the head-related transfer function (HRTF) provides cues that permit this discrimination, notably high frequency peaks and notches created by diffraction effects within the pinnae. For high quality binaural synthesis, HRTFs need to be individualized, matchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Greff and Katz [159] extended the above solutions to a multiple transducer array placed around each ear (8 speakers per ear) recreating the pinna-related component of the HRTF. Simulations and subjective evaluations showed that it is possible to excite the correct localization cues provided by the diffraction of the reconstructed wave front on the listener's own pinnae, using transducer driving filters related to a simple spherical head model.…”
Section: Unconventional Headphone Configurationsmentioning
confidence: 99%
“…Greff and Katz [159] extended the above solutions to a multiple transducer array placed around each ear (8 speakers per ear) recreating the pinna-related component of the HRTF. Simulations and subjective evaluations showed that it is possible to excite the correct localization cues provided by the diffraction of the reconstructed wave front on the listener's own pinnae, using transducer driving filters related to a simple spherical head model.…”
Section: Unconventional Headphone Configurationsmentioning
confidence: 99%